Letter (copy) - Citrine, Walter, 1887-1983
1940-12-14 038-0038-005 International. WMC/AC/DT/276. 14th December, 1940. Mr. C. Dukes, National Union of General and Municipal Workers, Woodfield, Copperkins Lane, Amersham, Bucks. Dear Mr. Dukes, I have your letter of the 11th of December in which you refer to a communication of yours of the 2nd instant with respect to an appeal for financial aid for Spanish refugee children. I have made full enquiries of our filing and postal departments and there is no record of this earlier communication of yours ever having been received. I can only assume that it has gone astray in the post, and I shall be grateful if you will let me have a copy. Yours sincerely, General Secretary. 292/946/38/38(V)